Signboards and the Naming of Small Businesses: Personhood and Dissimulation in a Sri Lankan Market Town - Luke Alexander Heslop (South Asia Multidisciplinary Academic Journal, 2015)
This paper concerns the naming of stalls in Sri Lanka’s largest wholesale vegetable market. Each optimistically selected business name, advertised on every carefully designed signboard, I argue, speaks to material and moral economies as well as nuanced perceptions of personhood. Signboards and the names they bear tell stories about the past and the future, success and shame, separation and loss, violence and dissimulation. In the context of the small business, I suggest selecting the name of the small business marks a separation intimately interwoven into the life courses of business families. The more sinister side of naming draws attention to the navigation of identity markers that have assumed new significance throughout the war in Sri Lanka, notably ethnicity and religion; as well as other less frequently documented markers of identity on the island that have existed relatively uninterrupted through times of conflict, namely caste.